Supramolecular polymer–molecule complexes as gain media for ultraviolet lasers - Lin, J; Zhu, G; Liu, B; Yu, M; Wang, X; Wang, L; Zhu, W; Xie, L; Xu, C; Wang, J; Stavrinou, P; Bradley, D; et al. (American Chemical Society, 2016)
A novel supramolecular system comprising a complex of 9,9′-diphenyl-9H,9′H-2,2′-bifluorene-9,9′-diol (DPFOH) with poly(methyl methacrylate) (PMMA) is presented as an attractive system for optical gain in the ultraviolet. The analogue compound 9,9′-diphenyl-9H,9′H-2,2′-bifluorene (DPFO8) without an -OH substituent was synthesized alongside DPFOH to confirm the importance of its chemical structure to the thin-film microstructure. A hydrogen-bonding interaction allows the molecule such as DPFOH and a combination of DPFOH and PMMA to have an excellent solution-processed high quality coating film. In stark contrast to the DPFO8 system, we find that the addition of 1 wt % DPFOH to PMMA leads to spontaneous formation of a supramolecular complex via hydrogen bonding interactions, giving rise to a homogeneous film with relatively high photoluminescence quantum efficiency ∼38 (±5)%. The demonstration of ultraviolet laser action with peak wavelength emission at 385 nm provided further evidence of the high optical quality of the DPFOH/PMMA supramolecular complex films. The DPFOH/PMMA supramolecular complex has great potential for use in low-cost solution-processed optoelectronic devices.